Evasion of Host Defence by Leishmania donovani: Subversion of Signaling Pathways. (7th April 2011) - Shadab, Md.; Ali, Nahid
Abstract : Protozoan parasites of the genus Leishmania are responsible for causing a variety of human diseases known as leishmaniasis, which range from self-healing skin lesions to severe infection of visceral organs that are often fatal if left untreated. Leishmania donovani ( L. donovani ), the causative agent of visceral leishmaniasis, exemplifys a devious organism that has developed the ability to invade and replicate within host macrophage. In fact, the parasite has evolved strategies to interfere with a broad range of signaling processes in macrophage that includes Protein Kinase C, the JAK2/STAT1 cascade, and the MAP Kinase pathway. This paper focuses on how L. donovani modulates these signaling pathways that favour its survival and persistence in host cells.